2016
DOI: 10.1039/c6cp00290k
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of NO˙ by small oxygen species HO2and O2˙: the role of negative charge, electronic spin and water solvation

Abstract: The reactions of HO2(-)(H2O)n and O2˙(-)(H2O)n clusters (n = 0-4) with NO˙ were studied experimentally using mass spectrometry; the experimental work was supported by quantum chemical computations for the case n = 0, 1. It was found that HO2(-)(H2O)n clusters were efficient in oxidizing NO˙ into NO2(-), although the reaction rate decreases rapidly with hydration above n = 1. Superoxide-water clusters did not oxidize NO˙ into NO2(-) under the present experimental conditions (low pressure): instead a reaction oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The oxidation of NO was found in reaction with the non‐hydrated HnormalO2 anion resulting in two reaction channels: NnormalO2 + OH, and OH − + NO 2 exothermic by 136 kJ mol −1 (1.41 eV) and 93 kJ mol −1 (0.96 eV), respectively . The NnormalO2 formation was found to be more efficient with a rate two orders of magnitude higher than OH − formation.…”
Section: Examples Of Atmospheric Cluster Studiesmentioning
confidence: 97%
See 2 more Smart Citations
“…The oxidation of NO was found in reaction with the non‐hydrated HnormalO2 anion resulting in two reaction channels: NnormalO2 + OH, and OH − + NO 2 exothermic by 136 kJ mol −1 (1.41 eV) and 93 kJ mol −1 (0.96 eV), respectively . The NnormalO2 formation was found to be more efficient with a rate two orders of magnitude higher than OH − formation.…”
Section: Examples Of Atmospheric Cluster Studiesmentioning
confidence: 97%
“…The reactions followed two pathways, one forming the peroxynitrite ONOO − anion and the other forming the nitrate NnormalO3 anion. Theoretical calculations showed that the ONOO − can isomerize to NnormalO3 with a substantial energy release around ≈240 kJ mol −1 (≈2.49 eV) …”
Section: Examples Of Atmospheric Cluster Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Equation 2, H 2 O may have an obvious effect by increasing the stability of reactant complexes, reducing the activation energy of transition states, [25] and having obviously solvent effects on the chemical reaction. [26][27][28][29] Thus, Butkovskaya et al [7] studied the effects of water monomer on the HO 2 + NO ! HNO 3 reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In Equation ), H 2 O may have an obvious effect by increasing the stability of reactant complexes, reducing the activation energy of transition states, [ 25 ] and having obviously solvent effects on the chemical reaction. [ 26–29 ] Thus, Butkovskaya et al [ 7 ] studied the effects of water monomer on the HO 2 + NO → HNO 3 reaction. In their work, the influence of water vapor on the production of HNO 3 in the gas‐phase HO 2 + NO reaction was determined at 298 K using a high‐pressure turbulent flow reactor coupled with a chemical ionization mass spectrometer.…”
Section: Introductionmentioning
confidence: 99%